Penerapan Algoritma Dijkstra Untuk Menentukan Rute Terpendek Dalam Distribusi Darah Di Palang Merah Indonesia Kota Palu Berbasis Mobile - Dival Maulana, Muhammad; Hendra, Andi; Yudhaswana, Yuri; Anshori, Yusuf; Ar. Lamasitudju, Chairunnisa (AI Society & STMIK Indonesia, 2024)
Efficient blood distribution is crucial for the Indonesian Red Cross (PMI) to save lives. This research develops a mobile-based blood distribution system that utilizes Dijkstra's Algorithm to determine the shortest delivery routes. The system is specifically designed for PMI in Palu City, assisting drivers in finding optimal paths and monitoring blood stock availability in hospitals in real-time. A prototyping method was employed for development, while the Google Maps API enables accurate route visualization. Research results indicate that Dijkstra's Algorithm reduces blood distribution time by 15-20% compared to the previously used manual methods. Additionally, this system facilitates better management of blood stocks and increases distribution speed. Blackbox testing ensures that all features function according to specifications. This research contributes to enhancing blood distribution efficiency at PMI, with the hope of minimizing the risk of blood shortages. Future research is recommended to further develop the system on a larger scale to address more complex distribution challenges.